One Day Service Land Registration After The Enforcement Of Decree Of The Head Of The National Land Agency Number 37/KEP-341/II/2014 Concerning The Quick Wins Program For The National Land Agency Bureaucracy Reform (Study At The Land Office Of Sidoarjo Regency) - Sunardi, Sunardi; Muhibbin, Moh.; Subandi, Subandi (Universitas Islam Malang, 2024)
Abstract : The One Day Service program through the Quick Wins program is a land service provided to the community aimed at changing work systems and mechanisms, mindset and work culture in a systematic and consistent manner in line with the goals and objectives of Bureaucratic Reform, so that in turn it can increase public trust in the Land Agency National Republic of Indonesia. The formulation of the problem in this thesis is 1) How is the Implementation of the One Day Service Land Registration Service After the Enactment of the Decree of the Head of the National Land Agency Number 37/Kep-341/II/2014 Regarding the Quick Wins Program for Bureaucratic Reform of the National Land Agency at the Land Office of Sidoarjo Regency and 2 ) What are the obstacles in implementing the One Day Service at the Sidoarjo Regency Land Office and how are the efforts to overcome these problems. This research is an empirical research with an empirical juridical approach and a horizontal and comparative approach. As for the results of the research on the Implementation of the One Day Service Land Registration Service After the Enactment of the Decree of the Head of the National Land Agency Number 37/Kep-341/II/2014 Concerning the Quick Wins Program Bureaucratic Reform of the National Land Agency At the Land Office of Sidoarjo Regency, the Applicant came to the Land Office with documents containing will be submitted, then, the Applicant goes to the registration counter to register, the Verifier file registration counter to do the Verification. If the files are complete, the files can be processed immediately and the Verifier officer immediately confirms in the land book section, then in the Land Book section the files are entered based on the files that have been entered and then in the land book section an SPS is issued, payment counter, the Applicant pays at the payment counter for his application based on the SPS given by the land book officer and then the applicant is given a receipt for proof of payment, the applicant then returns to the Verifier counter by showing the SPS and receipt proof of payment, only then the Verifier officer gives the STTD (Document Receipt) and the verifier officer gives confirmation in the printing department, after that the applicant's file goes to the printing department to be tidied up and determined in the land book regarding the type of application requested, such as the Roya application, Mortgage and so on for further analysis of the file, After completion of administration, the file d Submit it to the product submission counter, then the file is handed over to the applicant. The obstacles are the number of files submitted by the applicant which are incomplete so that verification is slow, the lack of facilities and infrastructure, especially the problem of counters and computerization so that the running of this program is not effective.Keywords, Land Registration, One Day Service